ADVANCING TOWARDS INDONESIA'S NET ZERO EMISSION GOALS: AN IN-DEPTH MULTI-CRITERIA DECISION MAKING (MCDM) ANALYSIS OF SHIP-LOADER OPERATIONS IN MARITIME TRANSPORTATION USING INTERVAL TYPE-2 FUZZY AHP AND TOPSIS METHODS - Septian Sudjono, Saint
Selecting an efficient ship loader is crucial for maritime transport, particularly for port operations. It involves evaluating key performance indicators (KPIs) such as loading rate, downtime, energy consumption, environmental impact, flexibility, initial and maintenance capital expenditures, throughput volume, and loading accuracy. These criteria are vital in choosing among various ship loader types—fixed, mobile, slew, parallel, shuttle, and tower. The right selection ensures optimal loading within the allowed laytime to avoid extra demurrage costs. The significance of this selection process is particularly highlighted in Indonesia, where efficient maritime logistics play a pivotal role in economic growth and development. A well-chosen ship loader not only enhances the Indonesian Marine Transportation PNBP by boosting dry bulk production but also supports the country's transition to cleaner energy. This is essential as Indonesia continues to increase fossil fuel production, such as coal, necessitating environmentally friendly operations with minimal spillage, dust, and noise. This study introduces a decision-making methodology combining the Interval Type2 Fuzzy Analytical Hierarchy Process (IT2FAHP) and the TOPSIS Method to address the multi-criteria decision-making challenges in ship loader selection. These methods leverage expert opinions, which can be subjective and uncertain, to evaluate and prioritize the KPIs and then rank the ship loader options. The research includes a sensitivity analysis to verify the robustness of decisions under various scenarios. Industry expert inputs were incorporated to ensure the methodology's applicability in real-world settings. The findings underscore the effectiveness of this combined approach in handling complex decisions where subjective judgments and uncertain information prevail. The study is pioneering in its systematic examination of operational and commercial aspects of ship loader selection in Indonesia, providing new insights into the most critical KPIs and identifying the parallel ship loader as 3 the most suitable option, despite the fixed loader's stability under stress tests. Overall, the IT2FAHP and TOPSIS methods not only offer a structured decision-making process for maritime transport engineering but also open avenues for further research in applying these techniques to other complex issues, enhancing decision-making in the field.